Local representatives 1968 - Strömberg, Lars (University of Gothenburg, 1983)
This survey forms part of the project ´Local government autonomy - local government boundaries´. Questions were asked about the assignment, opinion on the approaching amalgamation of municipalities and possible transmission of local government tasks to the State. Furthermore there were questions about the respondent´s attitude towards an increase or decrease of local authority achievements in a number of areas and also the respondent´s view on the attitudes of the electorate. The study was partly replicated in Local politicians 1979-1980 (SSD 0101).

Undersökningen ingår som en del i forskningsprogrammet 'Kommunal självstyrelse - kommunal indelning' och har liksom flertalet av kommunalforskningsgruppens övriga undersökningar företagits i ett särskilt kommunurval bestående av 36 kommuner i sex olika storleks- och tätortsklasser.
Enkäten - ställd till fullmäktigeledamöter valda i kommunalvalet 1966 i de 36 kommunerna - innehöll bland annat frågor om uppdrag; inställning till den förestående kommunsammanslagningen; eventuellt överförande av kommunala uppgifter till staten; den egna inställningen till ökning eller minskning av de kommunala insatserna på olika områden, samt vad man tror väljarna anser; attityder till kommunalpolitik; samt frågor om politikerrollen. Undersökningen har delvis replikerats 1980.
Kommunala förtroendemän 1968
Keywords: internal politics; inrikespolitik; Government, political systems and organisations; Regering, politiska system och organisationer; Social Sciences; Samhällsvetenskap; Political Science; Statsvetenskap